1988
DOI: 10.1002/pc.750090204
|View full text |Cite
|
Sign up to set email alerts
|

Theory of coalescence in immiscible polymer blends

Abstract: The theory of coalescence in melts of polymer blends was derived on the basis of the Smoluchowski theory for colloid systems. An approximation for a flux of particles used for solutions of colloids in water was analyzed. It is shown that this approximation cannot be used for polymer blends, and an approximation is suggested that could be justifiably used for them. A system of equations was derived for the time dependence of the number of individual i‐mers, using the relation suggested for the diffusion flux of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 6 publications
(3 reference statements)
2
47
0
Order By: Relevance
“…Multiblock copolymers showed higher improvement in impact strength and elongation at break in comparison with the diblock copolymer. Recently, Fortelny and Michá lková 14 studied the effect of the SBS compatibilizer as well as the rate and the time of mixing on the morphology of PP/PS blends with the weight ratio 75/25. They found that an admixture of the SBS copolymer led to the decrease in the average size of the dispersed PS particles, but, interestingly, it did not lead to an increase in the phase structure uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Multiblock copolymers showed higher improvement in impact strength and elongation at break in comparison with the diblock copolymer. Recently, Fortelny and Michá lková 14 studied the effect of the SBS compatibilizer as well as the rate and the time of mixing on the morphology of PP/PS blends with the weight ratio 75/25. They found that an admixture of the SBS copolymer led to the decrease in the average size of the dispersed PS particles, but, interestingly, it did not lead to an increase in the phase structure uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies between theoretical predictions on structure development and experimental results [4][5][6][7][8][9] are, most likely, due to the complex interfacial properties of, and the mutual interaction between, the polymers. In many cases mutual solubility is considered to be negligible for practical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases mutual solubility is considered to be negligible for practical purposes. [4][5][6][10][11][12] This seems reasonable since the polymers consist of long molecules, and mixing of those molecules is thermodynamically unfavorable. 13 Moreover, polymers possess a high ͑macroscopic͒ viscosity ͓typically from O͑1-10 3 ͒Pa s͔ and therefore mutual diffusion if present, is expected to be slow ͑the mutual diffusion coefficient is of the order of 10 −13 cm 2 / s and smaller 14 ͒.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersoid size has been found to increase linearly with the portion of the dispersed polymer when the portion is When a blend is left in its molten state, there is no longer a balance between the coalescence and break-up process, but coalescence dominates. The coalescence process resulting from collision between dispersoids due to Brownian motion in immiscible binary blends has been dealt with theoretically by S m o l u c h o w~k i .~~-~~ Furthermore, for a system of dispersed monospherical particles, it was found by Fortelny and Kovar26,27 that the inverse of the square root of the number of particles per unit volume (n) is proportional to the square root of the time ( t ) for which the coalescence has occurred such that where no is the initial number of spheres per unit area, k the Boltzmann constant, T the melt temperature, 7 viscosity of matrix polymer, and 4 the volume fraction of the dispersed polymer component.…”
mentioning
confidence: 98%